Plasma and cerebrospinal fluid tryptophan in multiple sclerosis and degenerative diseases. Issue 7 (July 1979) - Monaco, F; Fumero, S; Mondino, A; Mutani, R
Abstract : Tryptophan and competing neutral amino acid levels were found to be diminished in the plasma of patients with multiple sclerosis and degenerative diseases, the greatest decrease being of tryptophan. Cerebrospinal fluid tryptophan was decreased in multiple sclerosis and motor neurone disease, while leucine and valine were increased. These changes might lead to decreased synthesis of brain serotonin and brain proteins. The ratio between neutral amino acids and tryptophan might be used as an ancillary test in the screening of degenerative diseases.